2017
DOI: 10.4132/jptm.2017.04.24
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Status and Its Heterogeneity in Gastric Carcinoma of Vietnamese Patient

Abstract: BackgroundHuman epidermal growth factor receptor 2 (HER2) is related to the pathogenesis and poor outcome of numerous types of carcinomas, including gastric carcinoma. Gastric cancer patients with HER2 positivity have become potential candidates for targeted therapy with trastuzumab.MethodsWe investigated 208 gastric cancer specimens using immunohistochemistry (IHC), fluorescence in situ hybridization and dual in situ hybridization (ISH). We also investigated the concordance between IHC and ISH. The correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Some of the antibodies such as trastuzumab (an anti-human epidermal growth factor receptor 2 (HER2) antibody) and bevacizumab (an anti-vascular endothelial growth factor (VEGF) antibody) have been used for advanced gastric cancer [ 7 9 ]. However, these therapeutic antibodies do not treat all gastric cancer patients since less than 20% of gastric cancers showed HER2 gene amplification and approximately 25% of gastric cancers showed HER2 protein overexpression [ 10 ]. Furthermore, multiple clinical trials on the efficacies of trastuzumab and bevacizumab indicate that these antibodies may not improve the patient survival over chemotherapy alone [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the antibodies such as trastuzumab (an anti-human epidermal growth factor receptor 2 (HER2) antibody) and bevacizumab (an anti-vascular endothelial growth factor (VEGF) antibody) have been used for advanced gastric cancer [ 7 9 ]. However, these therapeutic antibodies do not treat all gastric cancer patients since less than 20% of gastric cancers showed HER2 gene amplification and approximately 25% of gastric cancers showed HER2 protein overexpression [ 10 ]. Furthermore, multiple clinical trials on the efficacies of trastuzumab and bevacizumab indicate that these antibodies may not improve the patient survival over chemotherapy alone [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,38 Anh Thu Phan et al reported a high level of concordance between ISH and IHC analyses, an amplification rate of the HER2 gene of 15.9% and protein overexpression of the HER2 gene of 24.5%, and elevated HER2 heterogeneity in gastric cancers (68.8% phenotypic heterogeneity and 57.6% genotypic heterogeneity). 38 HER2 positivity (overexpression [IHC3+] and/or gene amplification [FISH positive]) has been reported in 22% of advanced G/GEJ cancers but varies by tumor location and type in ToGA study, where HER2 staining (≤30% stained cells) by IHC was observed in almost 50% of cases. 14 Intratumoral phenotypic heterogeneity was also frequently observed with a high incidence of 63.5% in IHC 2+ cases and 28.3% in IHC 3+ cases, and phenotypic heterogeneity was more frequently observed than genotypic heterogeneity (48.8% vs. 26.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, variations in different study population ethnicity, cancer histotype, HER2 status evaluation assay utilization and tumor heterogeneity might produce divergent outcomes in sundry studies 2,38 . Anh Thu Phan et al reported a high level of concordance between ISH and IHC analyses, an amplification rate of the HER2 gene of 15.9% and protein overexpression of the HER2 gene of 24.5%, and elevated HER2 heterogeneity in gastric cancers (68.8% phenotypic heterogeneity and 57.6% genotypic heterogeneity) 38 . HER2 positivity (overexpression [IHC3+] and/or gene amplification [FISH positive]) has been reported in 22% of advanced G/GEJ cancers but varies by tumor location and type in ToGA study, where HER2 staining (≤30% stained cells) by IHC was observed in almost 50% of cases 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Her2 expression was detected in 6.6 percent of male patients and 10% of female patients in the current study but had no statistical significance. Phan et al [31] discovered that 26.6 percent of male and 20.3 percent of female patients have HER2. Roy et al [29] confirmed that Her2 was positive in 66% of males and 36% of females with no statistical significance.…”
Section: Discussionmentioning
confidence: 99%